The story of science in America - De Camp, L. Sprague (Lyon Sprague) 1907-; De Camp, Catherine Crook; Fisher, Leonard Everett (New York Scribner, 1967)
Describes the role of the inventor and naturalist in the United States from Colonial days to the middle of the nineteenth century, and then examines advances in physical, biological, and applied sciences made in the last one hundred years.
Bibliography: p. 270-274.
Keywords: Science -- History